CRITERES PHYSIOLOGIQUES DU STRESS A L’ABATTAGE CHEZ L’ESPECE OVINE - Oussama,KOURDRIA; Mabrouka,BOUSSETA (My University, 2022)
Pre-slaughter conditions are among the most stressful factors for livestock. Our study aims to assess stress reactions of 50 subjects of the ovine species; slaughtered under different conditions in terms of compliance and hygiene, at three zones: An open air slaughterhouse (Lot A), and two slaughterhouses (Lots B and C). The analysis of behavioral and physiological criteria (Heart rate, respiratory rate and body temperature) are measured after slaughter, in particular, on arrival and after unloading animals, while the blood and urine parameters (Cortisol, glycaemia and urinary glucose) were evaluated after bleeding. The results have showen that batch A recorded the highest rates of physiological criteria compared to batches B and C, which are respectively: (39.3° vs 39.1° and 38.6°) for body temperature, tachycardia (94.5 bpm vs 92 bpm; 87.85 bpm), as well as an increase in respiratory rate (51.7mvt/mnt 41mvt/m; 35.6mvt/mnt); which reflects extreme stress. Blood parameters recorded hypercortisolemia in the three batches (106.2 ng/dl, 95.2 nb/dl and 59.6 nb/dl respectively), hypoglycemia (47.4 mg/dl and 48.6mg/dl) in the two batches (A and B respectively) , having undergone prolonged food deprivation and (59.6 mg/dl) for LOT C. However, these variations are not significant (P>0.05). As well as a positive glycosuria is recorded in the three batches. When the correlation is very strong between the various parameters with significance at 0.01; of which positive for the T°; CR and cortisol, and negative for RR and glucose. Generally, all the data obtained testify to a modification in the physiological parameters of homeostasis, under the effect of the transport and slaughter conditions of the slaughterhouses surveyed, and therefore, a confirmation of an increased response to a state of pre-slaughter stress in sheep monitored.... تعد ظروف ما قبل الذبح من أكثر العوامل المسببة للتوتر لدى حيوانات المزرعة. تهدف هذه الدراسة إلى تقييم استجابة التوتر لدى 50 عينة من األغنام التي تم ذبحها في ظروف مختلفة من حيث مطابقة المعايير وشروط النظافة على مستوى ثالثة أماكن: مذبح عشوائي )القطيع أ( ومذبحان )القطيع ب وج(. تم تحليل االستجابة السلوكية والمعايير الفيزيولوجية )نبض القلب ٬ ومعدل النفس ٬ ودرجة حرارة الجسم( في مرحلة ما قبل الذبح ٬ وبالضبط عند الوصول ٬ وبعد إنزال الحيوانات ٬ بينما تم قياس معايير الدم والبول )هرمون التوتر ٬ ونسبة السكر في الدم ٬ونسبة السكر في البول( في مرحلة الذبح. أظهرت النتائج المتحصل عليها ارتفاع معدالت المقاييس الفيزيولوجية عند القطيع أ بالنسبة للقطيعين )ب( و)ج( والتي تمثلت في (39.3° و 39.1° و38.6°) بالنسبة لدرجة الحرارة ٬ وارتفاع معدل نبضات القلب (94.5 و 92 و 87.85 ضربة في الدقيقة) و (51.7 و 41 و35.6 نفس في الدقيقة) ما يعكس حالة توتر حاد. قياس معايير الدم أظهر ارتفاعا في نسبة هرمون التوتر لدى القطعان الثالثة )106.2 و95.2 و59.6( وأيضا انخفاضا في مستويات السكر في الدم لدى القطيعين )أ( و)ب( )47.4 و48.6على التوالي( الذين تم حرمانهما من األكل لفترة طويلة و )52.8( بالنسبة للقطيع )ج(. ومع ذلك يبقى هذا الفرق غير معتبر (0.05<P (كما تم تسجيل نتيجة ايجابية لدى فحص نسبة السكر في البول لدى جميع القطعان. ثبت وجود عالقة قوية بين مختلف المعايير المدروسة مع داللة ٬0.01 حيث توجد عالقة طردية بين درجة الحرارة٬ والنبض٬ والكورتيزول ٬ في حين أن العالقة بين التنفس والغلوكوز عالقة عكسية. على العموم٬ جميع النتائج المسجلة تثبت وجود تغير في المقاييس الفيزيولوجية لحالة توازن الوسط الداخلي تحت تأثير ظروف النقل٬ والذبح في المذابح التي تم تحريها٬ وبالتالي ثبوت وجود حالة من التوتر الشديد لدى األغنام المدروسة قبل ذبحها... Les conditions pré-abattage comptent parmi les facteurs les plus stressants pour les animaux d’élevage. Notre étude vise à évaluer les réactions au stress de 50 sujets de l’espèce ovine ; abattus dans des conditions différentes en termes de conformité et d’hygiène, au niveau de trois lieux d’abattage: une tuerie (Lot A), et deux abattoirs (Lots B et C). L’analyse des critères comportementaux et physiologiques (Rythme cardiaque, fréquence respiratoire et température corporelle) sont mesurés en près-abattage, notamment à l’arrivée et après le déchargement des animaux. Alors que les paramètres sanguins et urinaires (Cortisol, glycémie et glucose urinaire) se sont évalués après la saignée. Les résultats obtenus ont montré que le lot A a enregistré les moyennes les plus élevées des critères physiologiques par rapport aux lots B et C, qui sont respectivement: (39.3° vs 39.1°; 38.6°) pour la température, une tachycardie (94.5bpm vs 92bpm ; 87.85bpm), ainsi qu’une augmentation de la fréquence respiratoire (51.7mvt/m vs 41mvt/m ; 35.6mvt/m) ; ce qui reflète un stress extrême. Les paramètressanguins ont enregistré une hypercortisolémie chez les trois lots (106.2ng/dl, 95.2 nb/dlet59.6 nb/dl respectivement), une hypoglycémie (47.4 mg/dlet48.6mg/dl) chez les deux lots (A et B respectivement), ayant subis une privation alimentaire prolongée et (59.6 mg/dl) pour le LOT C. Cependant ces variations ne sont pas significatives (P>0.05). Ainsi qu’une glycosurie positiveest enregistrée chez les trois lots. Quant à la corrélation est très forte entres les divers paramètres avec signification à 0.01 ; dont positive pour la T° ; le RC et le cortisol, et négative pour le RR et le glucose. Généralement, toutes les données obtenues témoignent une modification dans les paramètres physiologiques de l’homéostasie, sous l’effet des conditions de transport et d’abattage des abattoirs enquêtés, et donc, une confirmation d’une réponse accrue à un état de stress pré abattage chez les ovins suivis